BIOENKAPSULASI PROBIOTIK (Lactobacillus casei) DENGAN POLLARD DAN TEPUNG TERIGU SERTA PENGARUHNYA TERHADAP VIABILITAS DAN LAJU PENGASAMAN [Bioencapsulation of Prebiotics (Lactobacillus casei) with Pollard and Wheat Flour and its Roles for the Acidificati] - Widodo ,; Soeparno ,; Endang Wahyuni (Jurnal Teknologi dan Industri Pangan, 2003)
BIOENKAPSULASI PROBIOTIK (Lactobacillus casei) DENGAN POLLARD DAN TEPUNG TERIGU SERTA PENGARUHNYA TERHADAP VIABILITAS DAN LAJU PENGASAMAN [Bioencapsulation of Prebiotics (Lactobacillus casei) with Pollard and Wheat Flour and its Roles for the Acidification Rate and Viability] An experimental was conducted in order to investigate the viability of bio-encapsulated probiotics Lactobacillus casei during yoghurt fermentation. Yoghurt fermentation was prepared on pasteurized 18% of skim milk medium and inoculated with 6% (v/v) of starters consisting of Lactobacillus bulgaricus. Streptococcus thermophillus and Lactobacillus casei with the proportion of 1:1:1 (v/v/v). Fermentation was conducted until the pH reached 4.5. Bioencapsulation was carried out through the formation of calcium-alginate bead gels with the addition of pollard or wheat flour. The results showed that bio-encapsulated probiotics took longer time (10 hours) to reach pH 4.5 as compared to non-bio-encapsulated  one (9 hoours). It also showed that bio-encapsulated probiotics with pollard resulted in a higher cell viabilyty after fermentation namely at 2.4 x 108 celss/g as compared to that encapsulated with wheat flour at 9.3 x 107 cells/g. Bio- encapsulation with pollard was able to maintain viability of prebiotics at 9.37 x 107 cells/g as compared to that of wheat flour and non filler encapsulation at 1.07 x 107 and 1.48 x 106 cells/g respectively. It was shown that alginate bio- encapsulation with addition of 2% (v/v) pollard or wheat flour can maintain probiotics viability up to 4 weeks. Keywords: bioencapsulation, probiotics viability, yoghurt fermentation